Non-word repetition and vocabulary in Kuwaiti Arabic-speaking children with down syndrome and typically developing children - Alsaber, Ahmad (2024)
Overview: Non-word repetition (NWR) is one of the most effective predictors of language impairments in children as it has been found to correlate with various language measures and the association between NWR and vocabulary is well documented in typically developing (TD) studies. However, there is a dire need for investigations of language skills in Kuwaiti Arabic individuals with Down Syndrome, and this study set out to fill a gap in this field. Method: In this paper, we compare the vocabulary and NWR skills of a group of 48 individuals with DS aged 6–20 years to a group of 44 TD children aged 3–10 years matched on nonverbal IQ. Furthermore, we investigate the correlations among these language measures in the two groups and examine whether NWR can predict receptive and expressive vocabulary in these two groups. Result: Results found DS participants performed significantly less than the TD group on the three language measures (receptive vocabulary t(90)= ?3.17, p <.01, expressive vocabulary t(90)= ?3.27, p <.01, and NWR t(90)= ?8.32, p <.01). Moreover, there were strong correlations between NWR and vocabulary (receptive and expressive) in the TD group but not the DS group. Conclusion: Findings supported the working memory model and the phonological processing account for the TD group. On the other hand, the poor association between NWR and vocabulary in the DS group might be due to poor phonological discrimination difficulties and speech discrimination difficulties.